2020
DOI: 10.2147/dmso.s235379
|View full text |Cite
|
Sign up to set email alerts
|

<p>Prevalence and Associated Factors of Metabolic Syndrome Among Patients with Severe Mental Illness at Hawassa, Southern-Ethiopia</p>

Abstract: Background: Patients with severe mental disorders have a high risk of metabolic-related complications like metabolic syndrome (MetS), diabetes mellitus (DM), hypertension and lipid derangements, and these factors may predispose them to a high mortality rate. Data is very scarce regarding MetS among patients with severe mental illness in Ethiopia. Therefore, this study aimed to assess the prevalence of MetS and its associated factors among patients with severe mental illness. Methods: A cross-sectional study wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
9
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 38 publications
5
9
2
Order By: Relevance
“…In addition, the present study revealed that participants of female sex were at higher risk of developing metabolic syndrome than those of male participants (AOR: 7.4, CI: 2.0, 27.6, p < 0.05). This result is consistent with the studies conducted in Kashmir [ 29 ], South Africa [ 46 ], South West Ethiopis [ 21 ] and Southern-Ethiopia [ 31 ]. Possible explanations for this gender disparity include differences in physiology, level of physical activity, and psychological factors between the male and female sexes.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In addition, the present study revealed that participants of female sex were at higher risk of developing metabolic syndrome than those of male participants (AOR: 7.4, CI: 2.0, 27.6, p < 0.05). This result is consistent with the studies conducted in Kashmir [ 29 ], South Africa [ 46 ], South West Ethiopis [ 21 ] and Southern-Ethiopia [ 31 ]. Possible explanations for this gender disparity include differences in physiology, level of physical activity, and psychological factors between the male and female sexes.…”
Section: Discussionsupporting
confidence: 92%
“…Adipose tissue possibly secretes many cytokines and reactive oxygen radicals, thus promoting inflammation and insulin resistance syndrome [ 44 , 49 , 50 ]. This finding was in line with the studies conducted in Southern Ethiopia [ 31 ] and Venezuela [ 51 ] ever alcohol intake was significantly associated with metabolic syndrome. However, this finding was in contrast with the study conducted in Jimma that found alcohol intake was not associated with metabolic syndrome [ 21 ].We speculate the difference could be due to the time variation, the socio-economic and cultural factors observed between the study participants.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The prevalence of MetS was estimated based on the IDF and NCEP/ATPIII criteria among the Ethiopian population of various study subjects. Fourteen studies reported the prevalence of MetS based on both IDF and NCEP/ATPIII criteria [ 36 – 44 , 48 50 , 54 , 56 ], seven studies based on NCEP/ATPIII criteria only [ 57 – 63 ], and again seven studies by IDF criteria only [ 45 47 , 51 53 , 55 ]. Table 3 presents the characteristics and outcomes of the reviewed studies.…”
Section: Resultsmentioning
confidence: 99%
“…All the included nine studies were cross sectional studies in their design. These studies were conducted across different countries of sub-Saharan Africa (two primary articles from Ethiopia [ 16 , 17 ], three from South Africa [ [18] , [19] , [20] ], two studies from Nigeria [ 21 , 22 ] and the rest two were from Ghana [ 23 ] and Uganda [ 24 ]. The sample size of primary studies included in this review was considerably variable ranging 88 to 450 participants ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%